Особливості житлової забудови Львова повоєнного періоду - Попова, С. Я.; Popova, S. (Видавництво Львівської політехніки, 2019)
У статті подано результати аналізу літературних та архівних джерел на тему житлової забудови Львова повоєнних років. Охарактеризовано соціально-політичні, культурні й економічні процеси і явища цього періоду та їх вплив на реалізацію загальної концепції житлової забудови Львова.

This article presents the results of analysis of published and archival sources on the topic of residential buildings design in Lviv in the early postwar years. Author describes the socio-political, cultural and economic processes and phenomena of this period. After returning to Lviv Soviet power in July 1944, it been tasked again to turn city into one of the industrial centers of the country. It was scheduled accelerated development of mechanical engineering, electrical, light, food and other industries. In Lviv was rebuilt and established all city economy. Construction was developed throughout city and covered all the places where the postwar ruins remained. At that time, the master plan for the city reconstruction had not yet been drawn up, the first master plan decisions were approved only in 1947. There was also no cartographic and planning material, new photos of the city territory, which complicated the work of architects. Lack of such data explained by the absence of Geodetic production office under the Office of the Chief Architect. But in 1946 this office was opened and in the same year there were carried out surveying work in the city. As is known from archival materials, the development of the scheme of first postwar master plan of the city was completed in 1948, but it has never been considered and approved by the government. This situation predetermined problems in the placement of industrial, residential and public facilities. In order to establish and control the establishment of new Soviet trends in architecture, an appropriate personnel policy was carried out. New leadership provided great value to political and educational work of creative collectives and citizens of the city. Systematically conducted lectures on topics which aimed at exploring new Soviet architecture, since it was implemented in practice. Established by the Soviet authorities, the totalitarian system covered all spheres of life, including architecture. The declared socialist realism style becomes the only allowed form of art, which was in practice set strict limitations and regulatory requirements. In the postwar period, due to the lack of funds for cities reconstruction the policy of maximum industrialization, unification and cheapening of housing construction was carried out. The author investigates the influence of these phenomena and processes on the general concept of residential development of Lviv in the postwar period. Housing construction in the postwar period was reduced to construction of house-inserts in the historical environment and several complex ensemble buildings in Stalinist Empire style, as well as complexes of low-rise typical buildings for workers of new industrial enterprises. This article describes the characteristics of buildings with average number of floors in the Stalinist Empire style. Residential buildings of Stalinist Empire style can be divided into two types: elite nomenclature and ordinary housing. The first ones were built for party elite and managers of enterprises, others for employees of enterprises. Most Stalinist residential buildings of Lviv belong to the second type. In general, residential buildings of this type are characterized by planning on the basis of typical sections (403-1, ordinary, corner and front sections), with the introduction of some changes caused by specific conditions. As part of the Soviet ideology and strict economy in housing construction, usually, the issues of laying roads, sidewalks, landscaping of adjacent areas, design of internal courtyards facades and apartments interiors was remained unresolved. Lack or poor quality of building and finishing materials led to faulty design of the facades and simplification of their decorative elements.
Characteristic features of residential buildings in lviv in the postwar period
Keywords: житлова забудова; сталінський ампір; соцреалізм; забудова середньої поверховості; типове планування; генеральний план міста; residental buildings; Stalinist Empire style; Socialist realism; average number of floors; typical planning; city master plan; 728.1